STRATEGI PEMBELAJARAN BAHASA ARAB DALAM MENGGUNAKAN MEDIA AUDIO-VISUAL GUNA MENINGKATKAN DAYA INGAT PESERTA DIDIK DI SEKOLAH THA-IT SUKSA, BANGKOK, THAILAND - Muhammad Hanif; Dzulfikar Rodafi; Rizcha Amalia Putri (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Arabic language learning is one of the three elements of language that students must master. Mufrodat learning plays an important role to support the success of language skills. But in fact, learning mufrodat still feels difficult in class 4/3 at Suksa Tha-IT school, Bangkok. Because the learning process is still monotonous and not pleasant. To overcome this, the researchers applied learning by using audio-visual media in learning Arabic to improve students' memory. This research consists of two stages, in collecting data using observation, interviews, and documentation. To check the validity of the data the author uses three ways, namely perseverance, observation, and triangulation. The source of the research was students from grade 4/3. The results showed that the application of audio-visual media can improve mastery of Mufrodat in 4/3 grade students at Suksa Tha-IT Bangkok, Thailand.